2014
DOI: 10.1371/journal.pone.0088295
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Short-Term and Long-Term Whole-Body Vibration in Healthy Men upon the Postural Stability

Abstract: The study aimed to establish the short-term and long-term effects of whole-body vibration on postural stability. The sample consisted of 28 male subjects randomly allocated to four comparative groups, three of which exercised on a vibration platform with parameters set individually for the groups. The stabilographic signal was recorded before the test commenced, after a single session of whole-body vibration, immediately after the last set of exercises of the 4-week whole-body vibration training, and one week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 33 publications
(63 reference statements)
0
33
0
2
Order By: Relevance
“…Balance and locomotion might also be improved by WBV application, as quantified (i) with center of pressure (COP) measures in static upright condition [for young healthy adults, see for example (3,15,16); for elderly, see for example (17)(18)(19)(20)], and (ii) with commonly-used clinical tests such as the singleleg-stance test, the Tinetti test, the Timed-Up-and-Go test, the Berg Balance Scale, and the Limits of stability. However, it is well-recognized that these classical clinical tests are subjective, show ceiling effects, and are usually not responsive enough to measure small progresses or deteriorations in a subject's ability to balance (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Balance and locomotion might also be improved by WBV application, as quantified (i) with center of pressure (COP) measures in static upright condition [for young healthy adults, see for example (3,15,16); for elderly, see for example (17)(18)(19)(20)], and (ii) with commonly-used clinical tests such as the singleleg-stance test, the Tinetti test, the Timed-Up-and-Go test, the Berg Balance Scale, and the Limits of stability. However, it is well-recognized that these classical clinical tests are subjective, show ceiling effects, and are usually not responsive enough to measure small progresses or deteriorations in a subject's ability to balance (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been carried out on the effects of WBV training on postural balance, in either healthy individuals (11), or sub-populations, such as elderly people (12), and patients with motor impairments due to stroke (13), cerebral palsy (14) or fibromyalgia (15). These studies present conflicting results, with some supporting its positive effects (11)(12)(13) and other showing no changes (16,17). To our knowledge, there are few studies investigating the effect of WBV during early rehabilitation after ACL reconstruction (18)(19)(20) and there is still discussion regarding the time span until the start of the rehabilitation protocol after surgery, duration of the programme or the exercise intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The suit employs the use of a tapping mechanism, which is much more advantageous over vibrator usage. Scientific research has shown that long term exposure to vibrations in a particular region would lead to a possible permanent dysfunction of the neural system present in that part of the body [15]. To counter this, tapping mechanism has opted for the Suit.…”
Section:  Tappersmentioning
confidence: 99%